2013
DOI: 10.1007/s40520-013-0075-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus conservative treatment of distal radius fractures in elderly

Abstract: The distal radius fractures (DRFs) are the second most common fracture in the elderly population. Despite their frequency, the optimal treatment of these fractures remains controversial. Several dogmatic myths on DRFs management may adversely affect their outcome and despite a strong trend versus surgical options, systematic reviews suggest that conservative treatment remains the safest option for DRFs in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…[23] Others concluded that conservative treatment remains the safest option in most cases. [24] In the present meta-analysis, no significant difference between internal fixation and conservative treatment were found. It was presently concluded that closed reduction and plaster immobilization are the best treatment of distal radius fracture.…”
Section: Discussioncontrasting
confidence: 50%
“…[23] Others concluded that conservative treatment remains the safest option in most cases. [24] In the present meta-analysis, no significant difference between internal fixation and conservative treatment were found. It was presently concluded that closed reduction and plaster immobilization are the best treatment of distal radius fracture.…”
Section: Discussioncontrasting
confidence: 50%